Proses Pembelajaran Teater Tradisional Lenong Pada Kelas X di SMA Negeri 11 Palembang - Yuningsih, Dwi; Hasan, Hasan; Ilhaq, Muhsin (Institut Teknologi Pendidikan Indonesia, 2022)
The problem in this research is how the process of learning traditional long theater in class X at SMA Negeri 11 Palembang, the research leads to a type of descriptive qualitative research. This study aims to find out and describe how the learning process for traditional lenong theater in class X at SMA Negeri 11 Palembang with the script